Microbial Diversity in Drought-Tolerant Sorghum Rhizobacteria - Kalindee S. Shinde (Research Perspectives of Microbiology and Biotechnology Vol. 9, 2025)
Little is known about the soil microbial diversity and the potential contribution of this microbial diversity to global biogeochemical cycling. Water deficit is the most common stress affecting plant growth in arid and semiarid regions. In the present investigation the microbial diversity particularly bacteria in the moisture stress (drought) soil environment depends on the types of host plant root on which these bacterial types colonize have been studied. Total 81 bacterial colonies isolated from sorghum and allied weed plants viz, Cassia cerassia, Fimbristylis miliacea, Argemone mexicana, Chrozophoro rottleri, Fumaria parviflora and Euphorbia esula using NA media. Out of which 42 were obtained as root endophytic isolates whereas 39 isolates were obtained as root ectophytic isolates. Soil samples were collected at the time of collection of root samples to determine the moisture stress status of the soil from the same fields having vertisols soil texture. All these endophytic and ectophytic bacterial culture were able to grow in in vitro condition at 13% soil moisture level indicating that they sustain the severe drought condition in soil. From this work it can be concluded that these moisture stress tolerant bacteria would be present and sustain under drought stress condition.